Les chercheurs face à la surveillance d’État : état des lieux et contre-mesures - Félix Tréguer; Camille Noûs (Tracés, 2019)
Since the 2013 disclosures of whistleblower Edward Snowden on the surveillance practices of Western intelligence agencies, the exposure of the field of social science to state surveillance – implemented by judiciary and police authorities, and more broadly justified by public safety imperatives – has received growing attention at the international level. Two major trends contribute to worsening such exposure: on the one hand, the anti-terrorist tide and the criminalization of social movements which, combined with technological change, lead to a multiplication of the surveillance capacities of security services; on the other hand, the inanity of the digital policies of higher education and research institutions, which contributes to reinforcing researchers’ dependence on digital oligopolies that are increasingly integrated into the State surveillance apparatus. This article provides a critical overview of the situation before dispensing some guidance on countermeasures aimed at reducing the risk that research data will be exposed to state surveillance.